VEHICLE TESTER PERFORMANCE OPTIMIZATION: THE ROLE OF TECHNICAL COMPETENCE AND THE IMPLEMENTATION OF STANDARD OPERATING PROCEDURES - Vivi Mariska Septiana; Dede Sunaryo (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study aims to analyze the influence of competence and the application of Standard Operating Procedures (SOP) on the performance of vehicle testers at the Tangerang Regency Transportation Office. This study is motivated by the importance of improving the quality of motor vehicle testing services, where human resource competence and procedural compliance are key factors. The research method uses an associative quantitative approach with census sampling techniques, involving all testing officers. Data were collected through questionnaires and observations, then analyzed by classical assumption tests and multiple linear regression. The results of the study show that both competence and the implementation of SOPs have a positive and significant effect on employee performance, both partially and simultaneously. These findings reinforce the human resource management theory that improved competence and procedural discipline can drive operational performance. This study provides practical contributions in the form of recommendations for improving competency-based training programs and strict supervision of the implementation of SOPs. The policy implications of this study can be a reference for relevant agencies in formulating strategies to improve service quality. The proportion of influence of other factors that were not studied opens up opportunities for further research by adding variables such as leadership or incentive systems.